Patience and Its Role in Human Life - Danish, Ahmadzia (Journal of Social Sciences - Kabul University, 2020)
Patience is one of the fundamental moral values in Islam and carries significant advantages. This article explores the role of patience in human life. It begins with a definition of patience, followed by an analysis of its value as emphasized in Quranic verses and the Sunnah of the Prophet (SAWS). The study also presents perspectives from modern Islamic scholars. The discussion covers various aspects of patience, including its types, degrees, benefits, and its influence on daily life. Furthermore, the article highlights instances of patience in the lives of Allah’s prophets as exemplary models for believers.